Chemical composition and antimicrobial activities of essential oil and ethanol extract of Cyperus fuscus L burs from Turkey - Erdem, Belgin; Bagci, Eyup; Dogan, Gulden; Aktoklu, Ekrem; Dayangac, Alpaslan (Pharmacotherapy Group, 2018)
Purpose: To investigate the chemical composition of the essential oil of Cyperus fuscus burs as well as the antimicrobial activities of the ethanol extracts and essential oil. Methods: Fresh burs roots of C. fuscus were collected at the flowering stage in an open area in Gudul (Ankara, Turkey). Preparation of the ethanol extract, hydrodistillation of the essential oil, GC-FID-MS analysis, and agar diffusion and MIC agar dilution assays were performed to determine various parameters for the oil and extracts. Results: The major compounds of the essential oil were dehydroaromadendrene (10.7 %), azulenone (8.5 %), alpha-selinene (7.5 %), alpha-ylangene (6.0 %) and beta-caryophyllene (5.6 %). The essential oil of Cyperus fuscus exhibited activity against Gram-negative bacteria with minimum inhibitory concentration (MIC) values ranging from 1000 to 31.25 mu l/mL. Similarly, the ethanol extract of the burs showed good antimicrobial activity with the MIC of the ethanol extracts on ranging from 1000 mu g/mL (Escherichia coli) to 250 mu g/mL (Pseudomonas. Aeruginosa, p < 0.05). However, the ethanol extract was inactive against yeast strains. Conclusion: Thus, the essential oil and ethanol extract of the studied plant can potentially be used as antimicrobial agent.
Keywords: Cyperus fuscus; Antimicrobial activity; Chemical composition; Essential oil